FEATURES OF FORMATION OF SOIL ELEMENT COMPOSITION IN CONTRAST GEOLOGICAL CONDITIONS (MZYMTA R., BLACK SEA COAST OF RUSSIA) - Zakharikhina, L.V. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
The Mzymta River (Black Sea coast, Russia) erodes different types of rocks. Among them, mudstones, siltstones and shales are predominating, and carbonate and clay-carbonate rocks are present in smaller quantities, and occasionally eruptive rocks are encountered. The area is characterized by the occurrence of polymetallic, gold, sulphide, rare-metal and rare-earth mineralization. The studies have shown that the differences in the quantitative and qualitative elemental composition of soils in the Mzymta River valley (determined by mass-spectrometric method for 61 elements) correlate with underlying rocks. The amount of rare-earth elements and their fractionation distinguishes soils formed on igneous or sedimentary soil-forming rocks. Ca/Mg ratio can be considered as a diagnostic sign of soils formed on clayey or carbonate rocks. The influence of ore mineralisation zones on soils is manifested in the close correlation of the main ore and associated elements (As, Co, Pb, Cu, Ni, Bi, Sb and Zn) with Fe and Al.